Inhibition of XPO1 enhances cell death induced by ABT‐199 in acute myeloid leukaemia via Mcl‐1. Issue 12 (14th September 2018) - Luedtke, Daniel A.; Su, Yongwei; Liu, Shuang; Edwards, Holly; Wang, Yue; Lin, Hai; Taub, Jeffrey W.; Ge, Yubin
Abstract: The antiapoptotic Bcl‐2 family proteins play critical roles in resistance to chemotherapy in acute myeloid leukaemia (AML). The Bcl‐2‐selective inhibitor ABT‐199 (Venetoclax) shows promising antileukaemic activity against AML, though Mcl‐1 limits its antileukaemic activity. XPO1 is a nuclear exporter overexpressed in AML cells and its inhibition decreases Mcl‐1 levels in cancer cells. Thus, we hypothesized that the XPO1‐selective inhibitor KPT‐330 (Selinexor) can synergize with ABT‐199 to induce apoptosis in AML cells through down‐regulation of Mcl‐1. The combination of KPT‐330 and ABT‐199 was found to synergistically induce apoptosis in AML cell lines and primary patient samples and cooperatively inhibit colony formation capacity of primary AML cells. KPT‐330 treatment decreased Mcl‐1 protein after apoptosis initiation. However, binding of Bim to Mcl‐1 induced by ABT‐199 was abrogated by KPT‐330 at the same time as apoptosis initiation. KPT‐330 treatment increased binding of Bcl‐2 to Bim but was overcome by ABT‐199 treatment, demonstrating that KPT‐330 and ABT‐199 reciprocally overcome apoptosis resistance. Mcl‐1 knockdown and overexpression confirmed its critical role in the antileukaemic activity of the combination. In summary, KPT‐330 treatment, alone and in combination with ABT‐199, modulates Mcl‐1, which plays an important role in the antileukaemic activity of the combination.